Chapter 12 Decolonising Science Communication in the Caribbean: Challenges and Transformations in Community- Based Engagement with Research on the ABCSSS Islands - Nava, Tibisay Sankatsing; Francisca, Roxanne-Liana; Oplaat, Krista T.; Bervoets, Tadzio (Bristol University Press, 2023)
Conversations around diversity, equity, and inclusion in science communication are in danger of generating much concern without effecting change and systematic transformations.